2008
DOI: 10.1161/atvbaha.107.159327
|View full text |Cite
|
Sign up to set email alerts
|

Role of Smooth Muscle Cells in the Initiation and Early Progression of Atherosclerosis

Abstract: Abstract-The initiation of atherosclerosis results from complex interactions of circulating factors and various cell types in the vessel wall, including endothelial cells, lymphocytes, monocytes, and smooth muscle cells (SMCs). Recent reviews highlight the role of activated endothelium and inflammatory cell recruitment in the initiation of and progression of early atherosclerosis. Yet, human autopsy studies, in vitro mechanistic studies, and in vivo correlative data suggest an important role for SMCs in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
577
2
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 716 publications
(607 citation statements)
references
References 111 publications
13
577
2
15
Order By: Relevance
“…17,38,39 In human atheroma, endothelial cells and smooth muscle cells also elaborate cytokines and contribute to the overall inflammatory state. 40,41 Therefore, it was logical to test whether or not reduced Rap1 levels can diminish the release of NFkB-mediated pro-inflammatory mediators in endothelial and vascular smooth muscle cells. Modulation of Rap1 levels had no effect on IL-8, IL-1b, ICAM-1, VCAM-1, E-selectin and Pselectin expression in activated endothelial cells and did not affect IL-8, IL-1b, M-CSF and GM-CSF expression in vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…17,38,39 In human atheroma, endothelial cells and smooth muscle cells also elaborate cytokines and contribute to the overall inflammatory state. 40,41 Therefore, it was logical to test whether or not reduced Rap1 levels can diminish the release of NFkB-mediated pro-inflammatory mediators in endothelial and vascular smooth muscle cells. Modulation of Rap1 levels had no effect on IL-8, IL-1b, ICAM-1, VCAM-1, E-selectin and Pselectin expression in activated endothelial cells and did not affect IL-8, IL-1b, M-CSF and GM-CSF expression in vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of an atherosclerotic plaque may result in myocardial infarction, stroke or peripheral vascular disease [22,23] . Atheroma formation involves endothelial damage, oxidized low density lipoprotein (LDL) infiltration, macrophage activation, collagen deposition, a change in the phenotype of VSMCs, as well as an increase in proliferative and migratory capability of VSMCs [4,5,24] . Previous studies have indicated that hyperglycemia is an important causative factor in the development of diabetic atherosclerosis, and high glucose levels appeared to be an important contributor to the functional impairment of VSMCs [2,5,25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Many cytokines, such as platelet-derived growth factor (PDGF), transforming growth factor-β (TGF-β), interferon γ (IFN γ) and monocyte chemotactic protein 1 (MCP-1), are secreted, which contributes to furthering the process of atherosclerosis [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, NGF and furin can be detected in rodent arteries and human proliferating VSMCs [90]. Proliferating VSMCs play a critical role in the atherosclerotic initiation and progression by influencing growth factor/cytokine synthesis and ECM production in the arterial wall [91]. Inhibition of furin leads to the enhanced proNGF and decreased b-NGF secretion, causing apoptosis, instead of migration, of proliferating VSMCs.…”
Section: Furin Promotes Cell Proliferation and Ecm Synthesis By Activmentioning
confidence: 99%